A Feasibility Study on the Use of Equine Chondrogenic Induced Mesenchymal Stem Cells as a Treatment for Natural Occurring Osteoarthritis in Dogs. (2nd June 2019) - Daems, Robert; Van Hecke, Lore; Schwarzkopf, Ilona; Depuydt, Eva; Broeckx, Sarah Y.; David, Michael; Beerts, Charlotte; Vandekerckhove, Peter; Spaas, Jan H.
Abstract : Conventional treatments of osteoarthritis (OA) reduce pain and the inflammatory response but do not repair the damaged cartilage. Xenogeneic peripheral blood-derived equine chondrogenically induced mesenchymal stem cells (ciMSC) could thus provide an interesting alternative. Six client-owned dogs with confirmed elbow OA were subjected to a baseline orthopedic examination, pressure plate analysis, general clinical examination, hematological analysis, synovial fluid sampling, and radiographic examination, and their owners completed two surveys. After all examinations, a 0.9% saline solution (placebo controlproduct = CP ) was administered intra-articularly. After 6 weeks, all examinations were repeated, owners again completed two surveys, and equine ciMSCs were administered in the same joint. After another 6 weeks, dogs were returned for a final follow-up. No serious adverse events or suspected adverse drug reactions were present during this study. No significant differences in blood analysis were noted between the CP and ciMSC treatment. Two adverse events were observed, both in the same dog, one after CP treatment and one after ciMSC treatment. The owner surveys revealed significantly less pain and lameness after ciMSC treatment compared to after CP treatment. There was no significant difference in the orthopedic examination parameters, the radiographic examination, synovial fluid sampling, and pressure plate analysis between CP treatment and ciMSC treatment. A single intra-articular administration of equine ciMSCs proved to be a well-tolerated treatment, which reduced lameness and pain according to the owner's evaluations compared to a placebo treatment.